Balancing Awareness and Interruption: Investigation of Notification Deferral Policies - Horvitz, Eric; Apacible, Johnson; Subramani, Muru (2005)
We review experiments with bounded deferral, a method aimed at reducing the disruptiveness of incoming messages and alerts in return for bounded delays in receiving information. Bounded deferral provides users with a means for balancing awareness about potentially urgent information with the cost of interruption.